2013
DOI: 10.1029/2012gl054340
|View full text |Cite
|
Sign up to set email alerts
|

Systematic changes in the incoming plate structure at the Kuril trench

Abstract: [1] Recent seismic structural studies in trench-outer rise regions have shown that V p within the incoming oceanic plate systematically decreases toward the trench, probably owing to bending and fracturing of the plate. To understand the mechanisms acting to reduce V p , V s is critical because the V p /V s ratio is a sensitive indicator of lithology, porosity, and the presence of fluid. In the outer rise region of the Kuril trench, we conducted an extensive seismic refraction and reflection survey that reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 111 publications
(143 citation statements)
references
References 30 publications
3
139
0
1
Order By: Relevance
“…Deploying three-component, short-period (4.5 Hz) sensors with a station spacing of 6 km, we constructed six linear OBS arrays in the northwestern Pacific for seismic exploration surveys during 2009 and 2010 (Fujie et al 2013 …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Deploying three-component, short-period (4.5 Hz) sensors with a station spacing of 6 km, we constructed six linear OBS arrays in the northwestern Pacific for seismic exploration surveys during 2009 and 2010 (Fujie et al 2013 …”
Section: Methodsmentioning
confidence: 99%
“…2c) by Fujie et al (2013). Fujie et al (2013) reported that the sub-seafloor structure in the southern part (x > 350 km) was formed near the spreading center and that the subseafloor structure around the region was deformed by magma-involved activity and normal faults during its formations. This explains the remarkably complex topography of the basement in the southern part, as shown in Fig.…”
Section: S Reflection Retrieval In the Northwestern Pacificmentioning
confidence: 99%
See 3 more Smart Citations